The phosphate solubilizing and N fixing Pantoea agglomerans bacteria affecting yield and biochemical properties including nutrient uptake of different tomato genotypes - Hamed Soltani; Akbar Hassani; Mohammad Baba Akbari Sari; Mehrdad Hanifei (Journal of Trace Elements and Minerals)
Background: Suggesting and testing innovative methods, which may enhance the growth and quality of crop plants in the field is of economic and health significance. Objectives and methods: There is not much data, to our knowledge, on the use of the endophytic bacteria, Pantoea agglomerans, affecting growth, yield and biochemical properties of different tomato (Solanum lycopersicum) genotypes (Rusha, Maranku, Hiro, and Vitara, supplied by the Zola Company, Holland) in the field conditions, as the objective of the present research. Different tomato growth and quality parameters including leaf greenness, number of flower, yield, fruit dissolved solids and dry biomass, pH, vitamin C, and nutrient uptake (N, P, K) were determined. Results: Genotype 3 followed by Genotype 4 indicated to be the most efficient ones with significantly higher tomato yield and nutrient uptake. The bacterial inoculation significantly increased tomato yield from a minimum of 7.58 kg plot−1 (control) to a maximum of 11.08 kg plot−1 (bacteria and Genotype 3). Interestingly, the highest vitamin C was resulted by the combination of the bacteria and Genotype 2 (15.53 mg 100g−1) and the least by the control treatment (12.18 mg 100g−1). The bacteria and Genotype 3 resulted in the highest N (3.76 and 4.46%) and P (0.38 and 0.52%) concentrations, and for K (2.67 and 3.83%) it was resulted by Genotype 1 and the bacteria. Fruit pH was negatively and significantly correlated with all the measured parameters. Conclusions: Although genotype was a determining factor significantly affecting tomato growth, yield and biochemical properties including nutrient uptake (N, P and K), its combination with P. agglomerans, intensified such enhancing effects. The tested bacterial strain, as a suitable biofertilization method, with respect to the compatibility of tomato genotype, is able to enhance tomato growth, yield and quality by affecting plant biochemical properties. The future research may look for the single and combined effects of P. agglomerans with the other PGPR strains on tomato quality and yield in different conditions including stress, which is of economic and health significance.